THE PHENOMENON OF ENGLISH USE IN INDONESIAN TELEVISION ADS: A SOCIOLUNGUISTICS STUDY - Mustofa, Ihyak; Nur Rohman, Tefur; Sohnui, Suhailee (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
This study explores the phenomenon of English use in Indonesian television advertisements, specifically analyzing the brand Kopi Good Day through a sociolinguistic approach. As globalization influences marketing strategies, the incorporation of foreign languages, particularly English, has become prevalent in Indonesia. While prior research has examined the effectiveness of foreign language advertising, there is a notable gap in understanding how this practice impacts local cultural values and consumer perceptions within Indonesia's multilingual context. The purpose of this study is to explore how attitudes and cultural identity among Indonesian audiences aged 18-35 are influenced by the use of the English language. To this effect, the present research has adopted a qualitative approach because it involves content analysis of selected Kopi Good Day advertisements and indepth interviews with around 20 to 30 individuals from various socio-economic backgrounds. The initial results show that 60% of the respondents believe that the use of the English language association makes the brand sound modern; while 30% are of the view that such an association will in due course undermine the cultural values at the local level. Another 70% said this would make the product more attractive and trendy for a younger audience, but 20% find it confusing since not everyone understands English very well. These findings testify to the greater complication in the interrelationship of global branding and local identity and point to the need for sensitivity on the part of advertisers to such dynamics. In this case, this study contributes to developing culturally sensitive advertising strategies that resonate with diverse consumer demographics in Indonesia, providing insights into how foreign language use in advertising can reflect and shape cultural identity in a rapidly globalizing society.